Genomics‐Guided Efficient Identification of 2,5‐Diketopiperazine Derivatives from Actinobacteria - Liu, Jing; Li, Shu‐Ming (Chembiochem : a European journal of chemical biology, 2023)
Secondary metabolites derived from microorganism constitute an important part of natural products. Mining of the microbial genomes revealed a large number of uncharacterized biosynthetic gene clusters, indicating their greater potential to synthetize specialized or secondary metabolites (SMs) than identified by classic fermentation and isolation approaches. Various bioinformatics tools have been developed to analyze and identify such gene clusters, thus accelerating significantly the mining process. Heterologous expression of an individual biosynthetic gene cluster has been proven as an efficient way to activate the genes and identify the encoded metabolites that cannot be detected under normal laboratory cultivation conditions. Herein, we describe a concept of genomics‐guided approach by performing genome mining and heterologous expression to uncover novel CDPS‐derived DKPs and functionally characterize novel tailoring enzymes embedded in the biosynthetic pathways. Recent works focused on the identification of the nucleobase‐related and dimeric DKPs are also presented. Genome mining combined with heterologous expression has been demonstrated to be an efficient way to identify novel 2,5‐diketopiperazine derivatives from actinobacteria. Meanwhile, their biosynthetic pathways and new enzymes embedded inside have been functionally characterized. It is expected that more biologically active diketopiperazines can be obtained by exploring the genetic potentials of microorganism in the future.